FACTORS THAT INFLUENCE THE DEVELOPMENT OF JUMIANG BEACH TOURIST AREA IN PAMEKASAN DISTRICT - Dewi Rupyanti Sinaga; Rimadewi Suprihardjo; Adjie Pamungkas (Journal of Architecture&ENVIRONMENT, 2015)
Jumiang Beach Tourist Area has tourism potentials that should be developed as one of the main coastal tourist areas in Pamekasan. The presence of ODTW and several diverse tourism potentials in Jumiang Beach Tourist Area may become the opportu-nities to further develop the tourism in Jumiang Beach. The absence of efforts to develop the utilization of tourist attraction, the lack of facilities and infrastructure supporting the tourist area, and the lack of interaction between the local community and the tourists who visit this beach indicate the absence of optimal development efforts. This article is a part of research on the formulation of the concept of development of Jumiang Beach Tourist Area in Pamekasan District. Through Content Analysis technique, the variables that influence the development of tourist areas were found. These variables were then transformed through descriptive-qualitative analysis to obtain the significant influential factors. The results showed that there were 8 (eight) factors that influence the development of Jumiang Beach Tourist Area: active participation of local community in tourism activities; improve-ment of coastal tourist attractions by utilizing the uniqueness in each tourist potential; presence of institutional managers of tourist areas; improvement the quality of  local community in supporting tourist activities; improvement the quality and quantity of tourism infrastructure and facilities; strengthening of marketing and promotion network quality; maintenance and improvement of environmental sustainability in coastal tourist area; and  formulation of supporting policies related to spatial factors.